Influence of The Level of Knowledge of BPJS Patients on The Use of JKN Mobile Applications in TP2RJ RSU Thalia Irham Gowa (Comprehensive Health Care, 2024)
Background : TheMobile JKN application is a new breakthrough developed by BPJS Kesehatan which provides convenience for participants to register or register in health services, take online queues, but there are still very few BPJS patients who use the Mobile application JKN data found that the total number of outpatient visits per day is 100 – 200 at Thalia Irham Goawa Hospital, only 10 – 15 use the JKN Mobile Application. Objective:To determine the influence of BPJS patients' knowledge level on the use of the Mobile JKN Application at TP2RJ. Method: This type of qualitative descriptive research with a simple linear regression analysis technique, a sample of 75 respondents, and an accidental sampling technique. Results: The results of simple linear regression showed a Significance Value = 0.000 < a probability value of 0.05 which means that there is an influence on the BPJS Patient Knowledge Level in TP2RJ, while the correlation value (R) = 0.688 and the determination coefficient (R Square) = 0.473, the following categories of independent variable influence strength (BPJS Patient Knowledge Level in TP2RJ) on the dependent variable show the strength of the influence magnitude is included in the category with a value of 0.30 – 0.50 (Utilization of Mobile JKN Application in TP2RJ): Conclusion: H0 rejected and Ha accepted there is an effect of BPJS patients' knowledge level on the utilization of the Mobile JKN Application, Meanwhile, the Knowledge Level variable has a moderate influence on the variable of the Utilization of the Mobile JKN Application in TP2RJ Keywords: JKN Mobile Application, Knowledge Level, Utilization